Assessing Language Appropriateness through Portfolios in Literature Classes - Bouras ,Rabah; Boumédiène, Houda (Faculty of Letters and Foreign Languages Department of English, 2023)
Teaching English literature has undergone significant changes and evolutions over time, presenting various challenges, including the issue of language appropriateness. The researcher's primary focus is assessing the language appropriateness of literature learners, particularly master one Students of the civilization and literature field of study at teliji amar in laghouat. The research employed a descriptive analytical approach, utilizing a questionnaire for master one students, a semi-structured interview for teachers of literature, and a written test to collect data for the sample targeted . The main findings demonstrate that portfolios can effectively address language appropriateness issues and improve language errors and mistakes. Reading, summarizing, and note taking were identified as effective strategies for enhancing the writing style of literature students. Ultimately, this research establishes English literature as a strong and dynamic platform that offers solutions to language issues and problems, ultimately improving the writing style of English language learners.